Interactions between endoplasmic reticulum stress and extracellular vesicles in multiple diseases - Ye, Jingyao; Liu, Xuehong (Frontiers in Immunology, 2022)
Immune responses can severely perturb endoplasmic reticulum (ER) function. As a protein-folding factory and dynamic calcium store,ER plays a pivotal role resisting pathogens and in immune diseases and various others diseases, such as cancer, cardiovascular diseases, neurological diseases, orthopedic diseases, liver-related diseases, metabolic disorders, and others. In recent years, an increasing number of studies have shown that extracellular vesicles (EVs) play important roles in these diseases, suggesting that cells carry out some physiological functions through EVs. The formation of EVs is dependent on the ER. ER stress, a state of protein imbalance,is both the cause and the result of the disease. ER stress can transmit pathological messages to the EVs, which are then delivered by EVs to target cells, leading to disease development. Moreover, EVs can transmit pathological messages to healthy cells, causing ER stress. This paper reviews the mechanisms underlying interactions between ER Stress and EVs in multiple diseases and their biological functions in multiple diseases. In addition, the prospects of these interactions indisease treatment are described.